Analisis Perilaku Sosial Remaja Yang Mengalami Broken Home Di RBN Wale Ma’zani - Kasenda, Rinna Yuanita; Wuner, Nasrani; Sasuwu, Chrispian; Senduk, Iren; Maarial, Amriani; Kesek, Marcella (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The purpose of this study was to find out how the social behavior of adolescents who experience a broken home at RBN WALE MA'ZANI Minahasa Walian I, Tomohon City, North Sulawesi. This type of research is case study research using qualitative methods with an interpretive phenomenological approach. Informants in this study amounted to 2 broken home teenagers with the technique of taking informants,namely purposive sampling. Data collection techniques, namely observation, interviews and documentation were carried out to analyze social behavior towards adolescents who experienced broken homes. The results of the study concluded that broken home adolescents at RBN WALE MA'ZANI Minahasa Walian I, Tomohon City, North Sulawesi, had bad behavior in the environment, feeling sad, depressed and one of the subjects also felt traumatized. The trauma that the subject felt left an impression on his mind and it was very difficult for the subject to forget. With the current condition of a broken home, it causes the subject's social behavior in the family, school and community to become worse.